Homosexuality as (Anti)Illness: Oscar Wilde's The Picture of Dorian Gray and Gabriele D'Annunzio's Il Piacere - Edward S. Brinkley (Studies in 20th & 21st Century Literature, 1998)
This article treats Oscar Wilde's The Picture of Dorian Gray as culturally antagonistic but also as culturally conservative: Dorian's liminal position as a male who knows—who has experienced sexual contact with other males—is linked in the text both to a position of cultural/epistemological superiority (the "Greek" sexual act constructed as index of canonical mastery, back to Greek texts and artwork) and to a position of disease and dis-figurement. The latter association, read by other commentators particularly in the final pages as punishment for narcissism, hedonism, or homosexual activity, is here glossed as an accusation against Victorian injunctions against same sex sexual activity constitutive of homosexual identity: the marks of disease accrue in the sphere of cultural representation, which then mark and mar the individual body. Dorian Gray as a text then launches a kind of "homosexual panic" on the part of subsequent writers in "decadent modernism," notably Gabriele D'Annunzio, whose Il Piacere attempts to re-valorize the ephebe as the bearer of canon—and must now do so as an avowedly heterosexual male, but in the context of the danger of the dandy: the Wilde figure as "Humphrey Heathfield" must be introduced in order to have been experienced, even if only in disgust. D'Annunzio's turn toward fascist politics is not accidental in this respect: the literary phenomenon of "fascist modernism" appears to hew very closely to the fear of the cultural ascendancy of the dandy, often read in such texts as a subcultural homosexual male, who must be both experienced and extinguished.
Keywords: Oscar Wilde; The Picture of Dorian Gray; culturally conservative; culturally antagonistic; male; know; sexual contact; cultural; epistemological; superiority; Greek; sexual act; disease; dis-figurement; homosexuality; Anti-Illness; illness; (Anti)illness; punishment; narcissism; hedonism; homosexual activity; Victorian injunctions; Victorian; same sex sexual activities; homosexual identity; marks of disease; cultural representation; individual body; body; homosexual panic; decadent modernism; modernism; Gabriele D' Annunzio; Il Piacere; ephebe; canon; dandy; danger of the dandy; Humphrey Heathfield; fascist politics; fascist modernism